Asignaciones salariales en el GAD Parroquial De San Juan durante el año 2020 - Gavilanes Cellan, Jennifer Melissa (2021)
The case study was carried out in the Autonomous Decentralized Parish Government of San Juan, an entity with public law; It has political, administrative and financial autonomy to carry out its activities for the benefit of citizens. The institution presents problems related to salary assignments such as effective salary payments, salary cuts to public servants, among others. The objective of the investigation is to identify the shortcomings that exist in terms of salary administration. The applied methodology has a mixed approach, accompanied by a descriptive scope. The types of documentary and field research were used, because they allowed to argue the case based on bibliographic support and to obtain direct information from primary sources, through interview and survey techniques; whose questionnaires were addressed to the president of the GAD and to the entity's collaborators. The main findings were: delay in the payment of salaries - salaries to human talent and suppliers, decrease in salary in certain jobs, modifications in the budget distribution, reduction of the institutional budget, lack of compliance with the LOTAIP and job demotivation. In conclusion, the management of the GAD has not been adequate in view of the budget reduction, influencing the normal operation of the institution and the fulfillment of objectives in the short and long term.